2013
DOI: 10.18489/sacj.v51i0.186
|View full text |Cite
|
Sign up to set email alerts
|

To Mature or not to Mature: The Information Systems Conundrum

Abstract: Research has been done within the South African information technology (IT) industry over the last decade with regard to project management maturity (PMM) and the impact it has on delivering information systems (IS) projects successfully. The research was done to determine whether IS PMM per knowledge area has improved over the last decade. It investigates if there is a correlation between maturity levels and project success. Four independent surveys over the last decade focused on IS PMM and the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 22 publications
1
3
0
Order By: Relevance
“…Only 72.2% of the project managers feel that they are competent enough to do proper risk management. These results correlate with previous studies on the maturity levels of risk management, and it was found that risk management is the least mature of all the knowledge areas (Marnewick 2013a). …”
Section: Monitoring and Controlling A Projectsupporting
confidence: 91%
“…Only 72.2% of the project managers feel that they are competent enough to do proper risk management. These results correlate with previous studies on the maturity levels of risk management, and it was found that risk management is the least mature of all the knowledge areas (Marnewick 2013a). …”
Section: Monitoring and Controlling A Projectsupporting
confidence: 91%
“…The project managers ranked themselves as competent in this area (93.5%). These results are in line with Marnewick (2013aMarnewick ( , 2013b where communication management was the most mature knowledge area.…”
Section: Communicatingsupporting
confidence: 88%
“…The success rates of IT projects in South Africa in 2003 (43%) and 2008 (37%) were not as impressive as that of 2011 (59%). The results of 2011 by C. Marnewick (2013) almost doubled the results of 2008 (from 37% to 59%). The success rate of 59%, and 29% were calculated as challenged, and the failure rate was 12%.…”
Section: Software Development Project Successmentioning
confidence: 79%
“…A study of the success rate of IT projects in South Africa was initially undertaken by Sonnekus and Labuschagne ( 2003) and thereafter taken over by C. Marnewick (2013). The study reports on IT projects in general, not restricted to software development projects.…”
Section: Software Development Project Successmentioning
confidence: 99%
See 1 more Smart Citation